THE EFFECTS OF THE PEDAGOGICAL EXPERIENCE ON THE QUALITY OF TEACHER EDUCATION - Tatjana Koteva-Mojsovska; Suzana Nikodinovska Bancotovska (International Journal of Cognitive Research in Science, Engineering and Education, 2015)
Faculties should ensure integration of science and teaching: science that constantly evolves following the changes in scientific thought and teaching that incorporates these changes in their own organization. So there is a need of including the students, who are prepare for teachers, in the process of pedagogical experience during their study. Pedagogical experience is a completed with a pedagogical practice and hospitation on one side and theoretical knowledge on the other side. Pedagogical experience is a kind of activities that students are involved in the educational process. Considering the importance of these activities, we made a research to determine the effects of pedagogical experience of students in the fourth year of studies at the Pedagogical Faculty in Skopje. This research is guided by two assumptions: 1. Pedagogical experience as an integral part of studies has positive effects on the quality of initial teacher education and educators; 2. The organization of pedagogical internship does not fully satisfy the educational-applicative needs of students and objectives of the internship. During the survey, we have found that the students have good theoretical knowledge about the educational process and are successful in selecting topics for discussion with the competent persons in institutions. But they are not initiative enough and they are not sufficiently active in the process that have no direct obligation to implement and to record. Because of that, students have to be well prepared and instructed for all activities through the practice that will relate to their overall engagement as teachers.It shows that there is a necessity to redefine the structure, objectives, content and organization of the internship.